Processing Nasals with and without Consecutive Context Phonemes: Evidence from Explicit Categorization and the N100 - Bien, Heidrun; Zwitserlood, Pienie (Frontiers in Psychology, 2013)
With neurophysiological (N100) and explicit behavioural measures (two-alternative forced-choice categorization), we investigated how the processing of nasal segments of German is affected by following context phonemes and their place of articulation. We investigated pre-lexical processing, with speech stimuli excised from naturally spoken utterances. Participants heard nasals (/n/, /m/, and place-assimilated /n’/), both with and without a subsequent context phoneme. Context phonemes were voiced or voiceless, and either shared or did not share their place of articulation with the nasals. The explicit forced-choice categorization of the isolated nasals showed /n’/ to be in-between the clear categorizations for /n/ and /m/. In early, implicit processing, /m/ had a significantly higher N100 amplitude than both /n/ and /n’/, with, most importantly, no difference between the latter two. When presented in context (e.g., /nb/, /mt/), explicit categorizations were affected by both the nasal and the context phoneme: a consecutive labial led to more M-categorizations, a following alveolar to more N-categorizations. The early processing of the nasal/+context stimuli in the N100 showed strong effects of context, modulated by the type of preceding nasal. Crucially, the context effects on assimilated nasals /n’/ were clearly different to effects on /m/, and indistinguishable from effects on /n/. The grouping of the isolated nasals in the N100 replicates previous findings, using MEG and a different set of stimuli. Importantly, the same grouping was observed in the nasal/+context stimuli. Most models that deal with assimilation are either challenged by the mere existence of phonemic context effects, and/or use mechanisms that rely on lexical information. Our results support the existence, and early activation, of pre-lexical categories for phonemic segments. We suggest that due to experience with assimilation, specific speech-sound categories are flexible enough to accept (or even i